Super-insulating, flame-retardant, and flexible poly(dimethylsiloxane) composites based on silica aerogel - Lee, Hyeseong; Lee, Doojin; Cho, Jaehyun; Kim, Young-O; Lim, Soonho; Youn, SangJun; Jung, Yong Chae; Kim, Seong Yun; Seong, Dong Gi (ELSEVIER SCI LTD, 2019)
Silica aerogels have attracted great interest for several decades because of their super thermal insulation property, but their fragility has limited their application in every-day products. Here we describe a method to fabricate flexible and thermally-insulated composites by using a flexible poly(dimethylsiloxane) (PDMS) matrix and by preventing matrix impregnation of the silica aerogel pores. The silica aerogel was first mixed with ethanol to prevent impregnation of the silica aerogel pores with PDMS molecules. After composite fabrication, the ethanol was removed. The optimum PDMS composite had super thermal insulation (0.018 W/m.K) and was flame-retardant, in addition to being flexible. This method described here will facilitate the application of silica aerogel-incorporated composites as thermal insulation materials for products that require flexibility and flame-retardant properties.